2015
DOI: 10.1159/000370027
|View full text |Cite
|
Sign up to set email alerts
|

Poor Tolerance and Limited Effects of Isosorbide-5-Mononitrate in Microvascular Angina

Abstract: Objectives: To assess the effects of isosorbide-5-mononitrate (ISMN) in patients with microvascular angina (MVA). Methods: We randomized 20 MVA patients, treated with a β-blocker or a calcium antagonist, to 60 mg slow-release ISMN (halved to 30 mg if not tolerated) or placebo once a day for 4 weeks; the patients were then switched to the other treatment for another 4 weeks. Their clinical status was assessed with the Seattle Angina Questionnaire (SAQ) and the EuroQoL score for quality of life. The exercise str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 17 publications
0
9
0
1
Order By: Relevance
“…A statistically significant improvement in quality of life was demonstrated in patients who continued the nitrate treatment. However, this improvement was not confirmed by the results of the exercise stress test or in the coronary microvascular and peripheral vascular function measurements [14] . Similar results for vascular functions and exercise stress tests have been reported with the sublingual administration of short-acting nitrates [15,16] .…”
mentioning
confidence: 85%
See 3 more Smart Citations
“…A statistically significant improvement in quality of life was demonstrated in patients who continued the nitrate treatment. However, this improvement was not confirmed by the results of the exercise stress test or in the coronary microvascular and peripheral vascular function measurements [14] . Similar results for vascular functions and exercise stress tests have been reported with the sublingual administration of short-acting nitrates [15,16] .…”
mentioning
confidence: 85%
“…Data on the effect of long-acting nitrates in the current literature are scarce; in the study by Lanza et al [13] , isosorbide-5-mononitrate was found to not be effective in controlling episodes of chest pain in patients with with the addition of isosorbide-5-mononitrate is important. However, due to a small study population and a high discontinuation rate of nitrate administration, the findings by Wu et al [14] on the clinical implication of routine use of long-acting nitrates in microvascular angina are questionable. More evidence is necessary to evaluate whether long-acting nitrates may become a routine medical approach for microvascular angina patients whose symptoms are not adequately controlled by first-line drug therapy.…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…It can cause a significant reduction in angina frequency, when compared to GTN, with complete eradication of acute angina episodes . However, ISMN showed reduced efficiency and tolerance rate in microvascular angina . These shortcomings have been associated with endothelial dysfunction and oxidative stress …”
Section: Nitric Oxide and Nitroxyl Donorsmentioning
confidence: 99%